How do you implicitly differentiate 2(x^2+y^2)/x = 3(x^2-y^2)/y?

1 Answer
Jun 15, 2016

dy/dx = 0.6359991

Explanation:

F(x,y)=2 (x^2 + y^2)/x - 3 (x^2 - y^2)/y = 0 is an homogeneous function so susbtituting y = lambda x we obtain

F(x, lambda x) = (x (-3 + 2 lambda+ 3 lambda^2 + 2lambda^3))/lambda = 0 with one real solution which is

lambda = 1/2 ((63 + 2 sqrt[993])^(1/3)/3^(2/3) - 1/(3 (63 + 2 sqrt[993]))^(1/3)-1)

discarding x=0,lambda=0 and considering only real values for lambda.

lambda =0.6359991.

F(x,y)=0 equiv y = 0.6359991 x

so dy/dx = 0.6359991